A vinylic rotaxane cross-linker for toughened network polymers from the radical polymerization of vinyl monomers. Issue 12 (22nd February 2017) - Sawada, J.; Aoki, D.; Kuzume, M.; Nakazono, K.; Otsuka, H.; Takata, T.
Abstract : A [2]rotaxane cross-linker with one vinyl group in each component was synthesized as a vinylic cross-linker for highly toughened network polymers. Abstract : A [2]rotaxane cross-linker (RC ) with one vinyl group in each component was designed and synthesized as a vinylic cross-linker for highly toughened network polymers, which were prepared from the radical polymerization of n -butyl acrylate and 2-ethylhexyl acrylate in the presence of 0.5 mol% ofRC .